Profil Hambatan Komunikasi Antar Budaya Peserta Didik Kelas VII di SMPN 3 Tebo - Andri Budiansah; Citra Imelda Usman; Fuaddillah Putra (Departement of Mathematics Education, 2023)
This research is motivated by the presence of students who have problems in communication, there are students who find it difficult to talk to their classmates because of language differences, and there are also students who do not socialize with their peers. The purpose of this study was to describe the barriers to intercultural communication among class VII students at SMPN 3 Tebo in terms of: 1) Language. 2) Emotions. 3) Culture. 4) Nonverbal This research was conducted using a quantitative descriptive method. The research population consisted of 224 students selected by purposive sampling technique with 64 participants. The instrument used is a questionnaire. As for data analysis using interval scores and percentages. Based on the results of research on barriers to intercultural communication of class VII students at SMPN 3 Tebo seen from: 1) barriers to intercultural communication seen from language are in the small category. 2) barriers to intercultural communication seen from emotions are in very few categories. 3) barriers to intercultural communication seen from language are in very few categories. 4) barriers to intercultural communication seen from language are in very few categories. This research is recommended for students to understand each other, understand and tolerate the cultural differences they have.